Prevalence, clinical manifestations, and associated factors of long COVID-19: Prevalencia, manifestaciones clínicas y factores asociados al COVID-19 de larga duración - Rojas-Bolivar, Daniel (2022)
The aim was to describe the prevalence, clinical manifestations, and associated factors of long-COVID. Bibliographic research of systematic reviews and meta-analyses was carried out in MEDLINE (through PubMed) until April 7th, 2022. 37 articles were found and 3 were included. Evidence quality was assessed via AMSTAR 2 criteria. Long-COVID prevalence is 43% (IC95%: 39% – 46%). Main clinical manifestations were weakness (41% [IC95%: 25% – 59%]), malaise (33% [IC95%: 15% – 57%]), fatigue (31% [IC95%: 24% – 39%]), concentration impairment (26% [IC95%: 21% – 32%]), and breathlessness (25% [IC95%: 18% – 34%]). Factors associated with long COVID were female sex, initial disease severity, age, and presence of comorbidities.